Material structure selection of blue organic light emitting diodes utilizing a hybrid experimental design - Shie, Jie Ren; Chittawanij, Apisit; Hong, Lin Ann; Lai, Chang Jun; Lai, Yun Jr; Juang, Fuh Shyang; Yeh, Pei Hsun; Tsai, Yu Sheng (My University, 2016)
A hybrid approach integrating a Taguchi orthogonal table with an irregular design of experiments (DOE) method was proposed for selecting an optimal material structure of blue organic light emitting diodes in order to achieve multi-objective quality characteristics of devices. Analysis of variance (ANOVA) was adopted to identify significant factors before regression models were obtained. Finally, an optimal material structure was determined by maximizing a desirability function relating to selected critical quality characteristics including the driving voltage, the luminance, and luminance efficiency.
Keywords: Analysis of variance; Blue organic light emitting diodes; Design of experiments; Material structure selection; Optimization; Taguchi method